NEW INEQUALITIES FOR LOCAL FRACTIONAL INTEGRALS PERTAINING GENERALIZED STRONGLY CONVEX MAPPINGS - Kashuri, Artion; Zeki Sarikaya, Mehmet (Matematichki Bilten, 2020)
In this paper, we first obtain a generalized integral identity for twice local fractional differentiable mappings on fractal sets \(\mathbb{R}^{α}\) (\(0